Global AIDS treatment drive takes off - Michael Fleshman (Africa Renewal, 2005)
When a reporter first met sevenyear-old Bongani in a hardscrabble shantytown near Johannesburg in 2003, it was evident the child was dying. He was too weak for school, stunted and racked by diarrhoea. There was little question that he, like his deceased parents, was infected with the human immunodeficiency virus that causes AIDS. It seemed equally certain that he would soon lie in a tiny grave next to theirs — joining the 370,000 South Africans who died from the disease that year.